Students’ Self-Reports on the Blended Learning Implementation at a Private University in Can Tho, Vietnam - Hong Van, Dao Thi; Minh Quan, Do Hoang; Mai Anh, Pham (Asian Journal of Arts and Culture, 2022)
This qualitative study was conducted to examine students’ self-reports about Blended Learning implementation at FPT University in Can Tho, Vietnam. It also conveyed learners’ attitudes toward the massive application of Blended Learning in other academic subjects. Relying on phenomenography theory, 324 students, who experienced Blended learning in the form of learning on Coursera, combining with lecturers’ offline mentoring, took part in the research by answering open-ended questions in an online survey. Data collection was analyzed based on Nguyen (2018). The results show that FPT University students have positive attitudes about their current Blended Learning courses, with most compliments for Blended Learing and its prominent features, including satisfying students’ curiosity about online learning, bringing students’ flexibility, and safety, especially in the time of the Covid-19 pandemic. Other negative responses related to online learning barriers, and students’ inclinations for traditional education.